Determination of land use and occupation, highlighting the Legal Reserve areas and urban zoning of the Ribeirão Candidópolis - MG watershed (Research, Society and Development, 2021)
The micro basin of Ribeirão Candidópolis is responsible for 55% of the urban supply of Itabira, the analysis of the environmental conditions of the basin is of great importance. Thus the determination of land use and occupation, highlighting aspects related to the Legal Reserve areas, as well as the situation of the urban and ecological zoning plan of the municipality of Itabira are parameters to analyze aspects of preservation and sustainable management in the basin. The use of Geographic Information System (GIS) tools for spatial analysis is of notable importance in this context, highlighting that the Legal Reserve areas are in approximately 20% of the rural properties as required by the Forest Code and that the reserves are in good conditions of preservation and use. Therefore, the current situation of the basin has not undergone major changes, the reserves show a great preservation of the areas of Legal Reserve, bearing in mind that it is necessary to strengthen the attention to the areas of pastures so that their growth does not affect the balance of the basin.